Bireta morozovi, a new species (Lepidoptera, Notodontidae) from China - Saldaitis, Aidas; Ivinskis, Povilas; Rimsaite, Jolanta (Zootaxa, 2011)
Over 30 species of the genus Bireta (Schintlmeister, 2008) are known from the Palearctic and neighbouring regions of Southeast Asia. Individual species of this genus are externally similar, but can be separated by characters of the male genitalia. Bireta are mostly distributed throughout Southeast Asia, especially China (Kiriakoff, 1962; Kobayashi & Kishida, 2004; Kobayashi, Kishida & Min, 2008; Schintlmeister & Fang, 2001) and Thailand (Schintlmeister, 2007). In Sichuan Province, China in the spring of 2010, the senior author collected a series of Bireta specimens which belongs to a new species, which is described below (acronyms for personal and institutional collections: AFM—Alessandro Floriani [Milan, Italy]; ASV—Aidas Saldaitis [Vilnius, Lithuania]; MWM/ZSM—Museum Thomas Witt [Munich, Germany]/Zoologische Staatssammlung, München [Germany]; NRCV—Nature Research Centre [Vilnius, Lithuania]; PMM—Pavel Morozov [Moscow, Russia]).